IFT trains in different stages of assembly queue at the ciliary base for consecutive release into the cilium - Wingfield, Jenna L; Mengoni, Ilaria; Bomberger, Heather; Jiang, Yu-Yang; Walsh, Jonathon D; Brown, Jason M; Picariello, Tyler; Cochran, Deborah A; Zhu, Bing; Pan, Junmin; Eggenschwiler, Jonathan; Gaertig, Jacek; et al. (eLife, 2017)
Intraflagellar transport (IFT) trains, multimegadalton assemblies of IFT proteins and motors, traffic proteins in cilia. To study how trains assemble, we employed fluorescence protein-tagged IFT proteins in Chlamydomonas reinhardtii. IFT-A and motor proteins are recruited from the cell body to the basal body pool, assembled into trains, move through the cilium, and disperse back into the cell body. In contrast to this ‘open’ system, IFT-B proteins from retrograde trains reenter the pool and a portion is reused directly in anterograde trains indicating a ‘semi-open’ system. Similar IFT systems were also observed in Tetrahymena thermophila and IMCD3 cells. FRAP analysis indicated that IFT proteins and motors of a given train are sequentially recruited to the basal bodies. IFT dynein and tubulin cargoes are loaded briefly before the trains depart. We conclude that the pool contains IFT trains in multiple stages of assembly queuing for successive release into the cilium upon completion.